The evaluation of basic training for civil servant candidates via online at the KHAN Development Center - Siregar, Waldi Ishaq (Community Empowerment, 2021)
Civil Servants (PNS) have a significant role in administering government, developing and managing natural resources, human resources, market opportunities and the democratic process. A professional civil servant profile is very urgent to be able to carry out their duties and authorities effectively and efficiently. During the Covid-19 pandemic that is currently engulfing the world, the civil servant candidates (CPNS) training learning system has changed from face-to-face to online methods. Therefore, an evaluation of this virtual system is needed in achieving the perfection of this CPNS basic training. The goals and objectives to be achieved in the basic training for CPNS group III is the achievement of the andragogy method. The final evaluation system was implemented by looking at the results of academic evaluations that are comprehensively recapitulated, including evaluation of behavioral attitudes, actualization and strengthening of technical competencies according to the field of assignment and their respective weighting to get the final score. Based on the final evaluation, 37 participants in the basic training of CPNS class III period XVII were declared graduated with an average grade of 92.59. From the implementation of the basic training, it can be concluded that all stages of the activity were carried out according to a previously prepared schedule. The number of participants who took part in training activities starting from the opening was 37 people and the results of the material provided by the teaching staff/widyaiswara were given a score satisfied by the participants. Furthermore, based on the results of the overall evaluation of the basic training participants, 32 people obtained the title "Very Satisfactory".